Amyloidosis cutis dyschromica: A rare dyschromic pigmentary disorder - Kuldeep Verma; Reena Kumari Sharma; Anchana Gulati; Mudita Gupta (Wolters Kluwer Medknow Publications, 2019)
Primary cutaneous amyloidosis (PCA) is the deposition of amyloid proteins in the skin without systemic involvement. Amyloidosis cutis dyschromica (ACD) is a rare variant of PCA with onset typically in early childhood or at a prepubertal age. It is more common in the Asian and Southeast Asian people. Clinically it manifests as asymptomatic diffuse hyperpigmentation interspersed with hypopigmented spots without papulation. Histologically, small foci of amyloid closely under the epidermis are seen. There are only few case reports in the literature of this rarer variant. We report a case of a 32-year-old male presenting as dyschromatosis with a prepubertal onset and histopathological evidence of intradermal deposits in the upper dermis which was confirmed on Congo red staining and hence was diagnosed as a case of ACD.